A history of war in 100 battles - Overy, R. J. (Oxford University Press, 2014)
Their very names--Gettysburg, Waterloo, Stalingrad--evoke images of great triumph and equally great suffering, moments when history seemed to hang in the balance. Considered in relation to each other, such battles--and others of less immediate renown--offer insight into the changing nature of armed combat, advances in technology, shifts in strategy and thought, as well as altered geopolitical landscapes. The most significant military engagements in history define the very nature of war. In his newest book, Richard Overy plumbs over 3,000 years of history, from the Fall of Troy in 1200 BC to th.